PENGARUH DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT.SUKA FAJAR LTD JAMBI - Reni Devita (Universitas Batanghari Jambi, 2016)
The average total absenteeism without explanation in the last five years as much as 0.14%. The average realized sales target achievement at PT. Suka Fajar Ltd Jambi in the last five years amounted to 71.21%. This fact shows that employees can achieve the target given to him.Indicators of discipline among others, the size of the compensation, the existence of exemplary leadership, whether there is a definite rule that can be used as a handle, courage leadership in taking action, presence or absence of supervision leaders, the presence or absence of attention to employees as well as the creation of habits that support the establishment of discipline. While performance indicators include the effective, efficient, quality, timeliness, productivity and safety.PT. Suka Fajar Ltd.Jambi is one company that is engaged in the automotive field. The company first gained the confidence to handle American vehicle is a car brand Ford. Seiiring the era of progress and improvement as well as development of business, PT. SukaFajar Ltd Jambi managed to enter into an agreement with PT. KTB which is the sole distributor of automotive brands Mitsubishi.Results SPSS 20 get the regression equation Y = -0.208 + 1.083 X. R2 value of 0.848 this number stating that the variable X or discipline capable of explaining the variable Y or performance of employees at PT. Suka Fajar Ltd Jambi amounted 84.80% 15.20% otherwise be caused by other variables outside variables studied. The correlation coefficient between disciplines on the performance of employees at PT. Suka Fajar Ltd Jambi is 0.921, meaning that there is a very close relationship between the variables X or Y or discipline and employee performance.Work discipline and performance of employees at PT. Suka Fajar Ltd Jambi high. Based on the test of hypothesis testing is known that there is significant influence between disciplines on the performance of employees at PT. Suka Fajar Ltd Jambi. Leaders should emphasize the importance of cooperation and communication with fellow employees. Thus, the synergy that will grow healthy and conducive working environment. Should be targeting the achievement of work must be neat and realistic. Thus, the employee will be more focused to achieve the output has been on target .Keyword : discipline, employee performance